Application of Pseudomonas Berfluoresen PfCasCas3-molase on Bananas: Adaptation Measures by the Dahlia Flower Farmer Group in National Food Security and Climate Change - Advinda, Linda; Putri, Dwi Hilda; Amelia, Kiki; Farma, Siska Alicia; Fevria, Resti; Putri, Santi Diana; Sari, Wilna (Fakultas MIPA Universitas Negeri Padang, 2025)
Nagari Pematang Panjang, located in Sijunjung Regency, is expected to become the center of banana production in Sijunjung Regency. BDB disease is one of the problems in banana cultivation in the Bunga Dahlia Farmer Group in Sijunjung. Until now, BDB has been treated with chemical pesticides or, in more severe cases, banana plants are usually destroyed. To overcome this BDB disease, the UNP community service team provided understanding through presentations on the dangers of using chemical pesticides to members of the Bunga Dahlia Farmer Group and provided the Pseudomonas fluorescens PfCasCas3-molase formula as a biocontrol agent. The presentation of materials was effective in increasing the understanding of farmer group members from 25.98% to 81.27%. The technological innovation in the form of the PfCasCas3-molase formula was successfully disseminated to the community